+0  
 
0
45
1
avatar

please help

 

 Apr 17, 2020
 #1
avatar+20810 
+1

( 3x ) / [ x2 + 2x + 1 ]  =  ( 3x ) / [ (x + 1)(x + 1) ]

 

( 2 ) / [ x2 - 1 ]  =  ( 2 ) / [ (x + 1)(x - 1) ]

 

The lowest common denominator is:  (x + 1)(x + 1)(x - 1)

 

Multiplying the top fraction by  (x - 1) / (x - 1):

  ( 3x ) / [ (x + 1)(x + 1) ]  ·  (x - 1) / (x - 1)  =  [ (3x)(x - 1) ] / [ (x + 1)(x + 1)(x - 1) ]  =  [ 3x2 - 3x ] / / [ (x + 1)(x + 1)(x - 1) ] 

 

Multiplying the bottom fraction by  (x + 1) / (x + 1)

  ( 2 ) / [ (x + 1)(x - 1) ] · (x + 1) / (x + 1)  =  [ (2)(x + 1) ] / [ (x + 1)(x - 1)(x + 1) ]  =   [ 2x + 2 ] / [ (x + 1)(x + 1)(x - 1) ] 

 

Subtracting the second from the first:  [  3x2 - 5x - 2 ] / [ (x + 1)(x + 1)(x - 1) ] 

 Apr 17, 2020

32 Online Users

avatar
avatar
avatar